INFLUENCE OF QUALITY OF ROLLED WIRE OF THE DRAWING TECHNOLOGICAL PARAMETERS ON THE PLASTICITY OF THE HIGH-STRENGTH WIRE - G. N. Katylkov (Литьë и металлургия)
The influence of the metal quality and technological factors of hardware production on the plasticity of high-strength wire is studied. A number of actions on the technology improvement have been realized on the basis of the received results.